Confocal depth‐resolved fluorescence micro‐X‐ray absorption spectroscopy for the study of cultural heritage materials: a new mobile endstation at the Beijing Synchrotron Radiation Facility. (10th August 2017) - Chen, Guang; Chu, Shengqi; Sun, Tianxi; Sun, Xuepeng; Zheng, Lirong; An, Pengfei; Zhu, Jian; Wu, Shurong; Du, Yonghua; Zhang, Jing
Abstract : The coloration mechanism of sacrificial red glaze has been investigated using confocal depth‐resolved micro‐X‐ray absorption spectroscopy at the 1W2B beamline of the Beijing Synchrotron Radiation Facility. Abstract : A confocal fluorescence endstation for depth‐resolved micro‐X‐ray absorption spectroscopy is described. A polycapillary half‐lens defines the incident beam path and a second polycapillary half‐lens at 90° defines the probe sample volume. An automatic alignment program based on an evolutionary algorithm is employed to make the alignment procedure efficient. This depth‐resolved system was examined on a general X‐ray absorption spectroscopy (XAS) beamline at the Beijing Synchrotron Radiation Facility. Sacrificial red glaze (AD 1368–1644) china was studied to show the capability of the instrument. As a mobile endstation to be applied on multiple beamlines, the confocal system can improve the function and flexibility of general XAS beamlines, and extend their capabilities to a wider user community.